Complete guide to life drawing - Bammes, Gottfried (Tunbridge Wells, Kent, Great Britain Search Press Ltd, 2011)
A comprehensive guide to human anatomy for artists that offers instructions for and illustrations of various techniques for sketching human figures
Study of proportion -- Principal proportions of the body -- Male figure in eometrical shapes -- Male figure : structural issues and exercises -- Male figure in profile -- Female figure -- Young female figure -- Young male figure -- The child's figure -- Infants (2-5 years) and pre-pubescent children (7-10 1/2 years) -- Young figures in sketchbook work -- Rest and movement -- Studies with a brush -- Contrapposto stance -- Exercises recommended for locomotive movement -- Different movements and solutions -- Legs and feet -- Overall structure -- Structure and mechanism of the knee joint -- Drawing the thigh and knee -- Structural shape of the foot skeleton -- Exercises in drawing feet -- The leg as a whole with its muscle groups and mass -- Exercises for studies of the leg -- Torso and shoulder girdle -- From the basic skeletal shape to the developed form -- Drawing the skeleton of the torso -- Shoulder girdle and rib cage -- The torso muscles -- Function and relief features of the abdomen -- Rear view of the torso -- Exercises in drawing the back view -- Arms and hands -- Proportions and overall structure of the arm -- The elbow joint (right) -- The skeleton of the arm (right) -- Simplifying the skeleton and mechanism of the forearm and wrist -- Proportions of the hand -- Schematic view of the muscles of the arm (right) -- Musculature of the arm -- Modelling of the arm by muscle groups -- Hand studies -- Head and neck -- Basic proportions of the head -- Relationship between the proportions of the head and the structure of the skull, front view -- Exploring the proportions of the living face -- Head proportions at various angles -- Exercises for proportion studies in profile -- Main features of the neck structure -- Main head shapes -- Muscles and the eyes -- The ear -- The mouth, with exercises in drawing the parts together -- Portraits and self-portraits -- Building up the whole figure -- Simple standing pose -- Dynamic standing pose -- Leaning poses -- Seated poses -- Reclining poses -- Sitting poses as expression of emotion
2
Keywords: ART -- Techniques -- Life Drawing; Figure drawing -- Technique; Human figure in art